Agentes alérgenos y su influencia en el asma bronquial, en niños de 0 a 5 años en la ciudadela Primero de Diciembre, Babahoyo Los Ríos, octubre 2018 – abril 2019. - Jaramillo Mora, Iraida Isabel (2019)
The purpose of the present investigation is to analyze how allergen agents influence bronchial asthma in children from 0 to 5 years old; and develop prevention techniques that manage to avoid complications and thus reduce infant mortality rates. For the analysis of this study it was necessary to use the deductive method due to the nature of the research, from this a quantitative approach was used to know the antecedents, and the evolution of bronchial asthma in children from 0 to 5 years to demonstrate the causes that influence this disease. Within the field research aspects and allergens agents that influence bronchial asthma were identified, considering that one of the problems that appears is the little knowledge that parents of children from 0 to 5 years and the inhabitants in general have about of bronchial asthma, do not have the necessary economic resources and lack of care or prevention techniques by specialized health, therefore the government should implement new prevention programs and qualified personnel to give talks to people to control bronchial asthma and reduce infant mortality rates in the country.